2013
DOI: 10.2174/156720513804871372
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Accumulation of Toxic Turn Amyloid-β is Associated with Endoplasmic Reticulum Stress in Alzheimer's Disease

Abstract: Amyloid-β protein (Aβ) accumulates in the neurons of Alzheimer's disease (AD) patients at an early stage of the disease. Recently, we found that Aβ with a toxic turn at positions 22 and 23 accumulates in neurons in AD brain. Here, we studied the accumulation of Aβ, toxic turn Aβ and high-molecular-weight Aβ oligomers in presenilin 1 (PS1) gene-transfected SH-SY5Y cells as well as in the brains of 3xTg-AD mice and AD patients. Immunostaining revealed that accumulation of toxic turn Aβ was promoted in G384A- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Recent evidence indicate that PrP misfolding in cellular models relevant to both infectious and hereditary prionoses affect ER Ca 2+ homeostasis and sensitize cells to endoplasmic reticulum stress [27]. Impaired intraneuronal Ca 2+ homeostasis, including increased ER Ca 2+ store levels is also a hallmark of AD pathogenesis and akin to our findings in APPPS1-21 mice upregulation of Grp78 was also described in two months old 3×Tg-AD tg mice in association with intraneuronal presence of Aβ aggregates [22]. Grp58 is a disulfide isomerase, which was shown to bind PrP Sc and prevent apoptosis through inhibiting caspase-12 activation [13].…”
Section: Discussionsupporting
confidence: 80%
“…Recent evidence indicate that PrP misfolding in cellular models relevant to both infectious and hereditary prionoses affect ER Ca 2+ homeostasis and sensitize cells to endoplasmic reticulum stress [27]. Impaired intraneuronal Ca 2+ homeostasis, including increased ER Ca 2+ store levels is also a hallmark of AD pathogenesis and akin to our findings in APPPS1-21 mice upregulation of Grp78 was also described in two months old 3×Tg-AD tg mice in association with intraneuronal presence of Aβ aggregates [22]. Grp58 is a disulfide isomerase, which was shown to bind PrP Sc and prevent apoptosis through inhibiting caspase-12 activation [13].…”
Section: Discussionsupporting
confidence: 80%
“…Ohyagi and colleagues showed that intraneuronal staining by 11A1 was more closely related to the onset of memory impairment in 3xTg-AD mice than that by 4G8. 120 is thus a unique antibody that preferably recognizes intracellular amyloid in the human brain along with senile plaques. These findings highlight that the toxic conformer of Aβ42 could accumulate within neurons at the early stage during AD progression.…”
Section: Intracellular Aβmentioning
confidence: 99%
“…The potential mechanisms of action of (+)SKF-10,047 on increasing mitochondrial movement should be evaluated, including effects on mitochondrial ATP production and interaction with mitochondrial motor proteins. The relationship of reduced mitochondrial number and movement to ER stress should also be examined, as ER stress markers are increased in 3xTg-AD mice as early as 2 months of age [40]. σ 1 R attenuate ER stress [41] and could potentially exert their mitochondrial effects through this pathway.…”
Section: Discussionmentioning
confidence: 99%